2020
DOI: 10.3390/molecules25061264
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Characterization of Phenolamines and Flavonoids from Rape Bee Pollen, and Comparison of Their Antioxidant Activities and Protective Effects Against Oxidative Stress

Abstract: Phenolamines and flavonoids are two important components in bee pollen. There are many reports on the bioactivity of flavonoids in bee pollen, but few on phenolamines. This study aims to separate and characterize the flavonoids and phenolamines from rape bee pollen, and compare their antioxidant activities and protective effects against oxidative stress. The rape bee pollen was separated to obtain 35% and 50% fractions, which were characterized by HPLC-ESI-QTOF-MS/MS. The results showed that the compounds in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 35 publications
3
31
0
Order By: Relevance
“…Nevertheless, analysis of the Atsht mutant showed no alteration of free polyamine levels (Fellenberg et al, 2012). Experiments done in vitro with phenolamides extracted and partially purified from bee pollen evidenced the putative role of these molecules in oxidative stress protection (Zhang et al, 2020). Additionally, some antifungal properties were also reported for phenolamides accumulated at the surface of sunflower pollen (Kyselka et al, 2018).…”
Section: Phenolamides In Relation To Floral Initiation and Flower Fermentioning
confidence: 99%
“…Nevertheless, analysis of the Atsht mutant showed no alteration of free polyamine levels (Fellenberg et al, 2012). Experiments done in vitro with phenolamides extracted and partially purified from bee pollen evidenced the putative role of these molecules in oxidative stress protection (Zhang et al, 2020). Additionally, some antifungal properties were also reported for phenolamides accumulated at the surface of sunflower pollen (Kyselka et al, 2018).…”
Section: Phenolamides In Relation To Floral Initiation and Flower Fermentioning
confidence: 99%
“…Previous studies reported that BCP has a variety of valuable nutritional features and therapeutic effects ( Khalifa et al, 2020 ; Thakur and Nanda, 2020 ), including those ameliorating the gut barrier function and the immune system within the gastrointestinal tract, the treatment of inflammatory status, and the prevention of oxidative stress damages ( Chen et al, 2019 ; Li et al, 2019 ; Zhang et al, 2020 ). Beneficial effects of bioactive compounds from BCP depend on their bioaccessibility, which is defined as the amount released during digestion from the food matrix, and made available for small intestinal absorption.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial functional properties of Started-BCP are likely attributable to the greater bioaccessibility of inherent bioactive compounds, like phenolics. BCP represents a valuable reservoir of phenolic compounds, especially flavonoids, phenolic acids, and phenolamines, which have been shown to scavenge free radicals and ROS, and protect against oxidative stress injury ( Zhang et al, 2020 ). Independently of their antioxidant activity, phenolics are also able to interfer with inflammatory transduction pathways, by interacting with intracellular signaling cascades or by binding to the ATP-binding sites of several proteins ( Bouayed and Bohn, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, N' , N'' -bis-(5-hydroxyferuloyl)- N''' -sinapoyl spermidine has low abundance in most genotypes of clade B and clade C, indicating possible functional differentiation of the CYP98A family in those genotypes. Di-coumaroyl and tri-coumaroyl spermidine, which are considered as markers of male fertility are abundant in anther ( Werner et al, 1995 ), and rape bee pollen nectar ( Zhang et al, 2020 ). In this study, the proportion of di-coumaroyl spermidine in clade C genotypes was much higher than that in clade A and B, indicating the species in clade C may attract higher bee visitation.…”
Section: Discussionmentioning
confidence: 99%